Gloomy Images of Yellow and Żółty in a Corpus-Based Cognitive Study - Gieroń-Czepczor, Ewa (Research in Language, 2013)
The paper reports on a comparative corpus-based semantic analysis of one colour term as it is used in two languages: English yellow and Polish żółty. The investigation of central and peripheral meanings, based on analyses of corpus concordances draws upon the methodology and constructs of cognitive linguistics, such as prototype-based categories, domains, conceptual metonymy and metaphor. The first objective of this parallel study is to determine the prototypical reference points for yellow and żółty, followed by descriptions of those motivations and mechanisms of meaning extensions which lead to ‘figurative’ usages. The results are tentatively suggested in the form of a general network of related meanings, the entrenchments of which are established on the basis of frequencies attested in samples of 1,500 citations. The outcomes confirm a conceptual proximity reflected in the semantics of these colour terms, which seems to be – perhaps surprisingly – incongruous with the popular association of yellow/żółty with the sun. As the evidence provided by the British National Corpus and the Polish Scientific Publishers' corpus (PWN) reveals, the central and peripheral readings are inspired by the imagery of autumnal and physiological changes, while the semantics of both yellow and żółty reflect the significant influence of cultural factors, unparalleled in the polysemies of the other five basic colour terms.